2009
DOI: 10.1509/jppm.28.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Eating with a Purpose: Consumer Response to Functional Food Health Claims in Conflicting versus Complementary Information Environments

Abstract: Marketers of food products have recently introduced a variety of "functional foods" that promise consumers improvements in targeted physiological functions. However, despite the proliferation of functional food health claims promising more than basic nutrition, little is known about consumer responses to these claims, particularly in information environments in which inconsistent information may be available about the efficacy of a particular functional ingredient. Across two studies, the authors demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 54 publications
(86 reference statements)
3
81
0
Order By: Relevance
“…Our results extend the results of Naylor et al (2009) in the context of ecological consumption. Indeed, similar patterns of evaluations were found between HEC consumers and highly health-conscious consumers when confronted with conflicting information targeting an important issue.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results extend the results of Naylor et al (2009) in the context of ecological consumption. Indeed, similar patterns of evaluations were found between HEC consumers and highly health-conscious consumers when confronted with conflicting information targeting an important issue.…”
Section: Discussionsupporting
confidence: 88%
“…Rettie and Brewer (2000) propose a slightly different division into visual (e.g., appearance, images) and verbal package elements (e.g., claims and descriptions). We adhere to this division as visual and verbal packaging signals have been reported to influence consumer responses (Kauppinen-R€ ais€ anen, 2014;Naylor, Droms, & Haws, 2009;Orth & Malkewitz, 2008;Wansink, Sonka, & Hasler, 2004).…”
Section: The Effect Of Visual and Verbal Design Elements On Consumersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moorman et al (2008) found that after reading the conflicting information from newspaper about the function of vitamin B6, the confidences of consumers for the experts would decline [8]. Naylor et al (2009) demonstrated that, compared to consumers with higher health consciousness, consumers with lower health consciousness significantly lower their likelihood of choosing a functional over a nonfunctional food when faced with conflicting (versus complementary) information [9].…”
Section: The Influence Of Conflicting Information On Consumermentioning
confidence: 99%
“…According to cognitive dissonance theory, the conflicting information requires consumers for more cognitive resources, the more conflict, the more cognitive resources required (Heckler& Childers, 1992; Meyers-Levy & Tybout, 1989) [9] [11]. Compared to consistent information, conflicting information can lead to more ambivalent attitude (Klaus Jonas and Michael Diehl, 1997) [12].…”
Section: The Influence Of Conflicting Information On Consumermentioning
confidence: 99%